"Poetic Discourse and Sound Modeling in Ramād al-Shams - laaraj, mahdi (El Omda in Linguistics and Discourse Analysis, 2018)
In poetry, as in other genres of literature and art, structure must be granted fundamental and special importance. Revealing and identifying the structures of texts and the nature of their functioning not only gives value to reading and reception—including various critical activities and theoretical formulation—but also endows the texts themselves with their essential and intrinsic value. Yet, what does artistic structure mean in a text? What are the limits of this structure? Indeed, what are the boundaries of the concept of the artistic text itself?